Nonlinear elliptic equations related to weighted sum operators. (May 2020) - Di Fazio, G.; Fanciullo, M.S.; Zamboni, P.
Abstract: We study a new kind of degenerate operators related to some weighted sum operators. Although the operators are severely degenerate we show the smoothness of the weak solutions.